Prediction and Analysis of Lake Ice Phenology Dynamics Under Future Climate Scenarios Across the Inner Tibetan Plateau. Issue 23 (27th November 2020) - Ruan, Yongjian; Zhang, Xinchang; Xin, Qinchuan; Qiu, Yubao; Sun, Ying
Abstract: How climate change influences lake ice phenology is important in understanding the climate‐lake interactions. This study investigates the response of lake ice phenology to future climate scenarios. Thirty‐five lakes in the Tibetan Plateau were studied. Firstly, we applied a random forest (RF) model to simulate lake ice condition under different representative concentration pathways (RCPs). The results of the virtual experiments show that lake ice freeze‐up start date (FUSD) and break‐up end date (BUED) are well simulated by the RF model, with R 2 FUSD  > 0.91 under different RCPs, and R 2 BUED  > 0.84, except in RCP2.6 (R 2  = 0.74). Secondly, two non‐parametric methods (Mann‐Kendall and Sen's slope estimator) were used for analyzing the trends in lake ice phenology and its response to various emission scenarios. Lake ice phenology was largely affected by temperature changes under different RCPs, and it had a larger inter‐annual variability in the early period (2002–2050) than in the later period (2050–2099). FUSD of 35 lakes delayed by an average of 0.01, 0.04, and 0.04 days/yr from 2002 to 2098 under RCP4.5, RCP6.0, and RCP8.5, whereas BUED advanced by an average of 0.04, 0.11, and 0.21 days/yr from 2003 to 2099. Both delays in FUSD and advances in BUED contributed to shortened average ice duration of 35 lakes, which shortened by 0.05, 0.14, and 0.25 days/yr from 2002 to 2098 under RCP4.5, RCP6.0, and RCP8.5, respectively. These findings could help to tackle the impacts of climate change on the lake systems. Plain Language Summary: The impacts of future climate scenarios on lake ice phenology is important in understanding the climate‐lake interactions. Thirty‐five lakes in the Tibetan Plateau were studied. We employed a random forest (RF) model to simulate lake ice condition under different representative concentration pathways (RCPs). The results of the virtual experiments show that lake ice freeze‐up start date (FUSD) and break‐up end date (BUED) are well simulated by the RF model, under different RCPs. FUSD of 35 lakes delayed by an average of 0.01, 0.04, and 0.04 days/yr from 2002 to 2098 under RCP4.5, RCP6.0, and RCP8.5, whereas BUED advanced by an average of 0.04, 0.11, and 0.21 days/yr from 2003 to 2099. Both delays in FUSD and advances in BUED contributed to shortened average ice duration of 35 lakes, which shortened by 0.05, 0.14, and 0.25 days/yr from 2003 to 2098 under RCP4.5, RCP6.0, and RCP8.5, respectively. Our results could help to tackle the impacts of climate change on the lake systems. Key Points: The pace of lake ice phenology change showed quite different characteristics across six sub‐basins in the inner TP Advances in break‐up end date and delays in freeze‐up start date result in shortened ice duration under RCP4.5/6.0/8.5 Inter‐annual variation of lake ice phenology increases with increasing CO2 concentration in the air